Men and Women's Occupational Activities and the Risk of Developing Osteoarthritis of the Knee, Hip, or Hands: A Systematic Review and Recommendations for Future Research. Issue 3 (27th February 2020) - Gignac, Monique A. M.; Irvin, Emma; Cullen, Kim; Van Eerd, Dwayne; Beaton, Dorcas E.; Mahood, Quenby; McLeod, Chris; Backman, Catherine L.
Abstract : Objective: To systematically review the evidence for an increased risk of osteoarthritis in the hip, knee, hand, wrist, finger, ankle, foot, shoulder, neck, and spine related to diverse occupational activities of men and women and to examine dose‐response information related to the frequency, intensity, and duration of work exposures and the risk of osteoarthritis (OA). Methods: Established guidelines for systematic reviews in occupational health and safety studies were followed. MEDLINE, Embase, CINAHL, and Cochrane Library were searched from inception to December 2017. Studies were reviewed for relevance, quality was appraised, and data were extracted and synthesized. Results: Sixty‐nine studies from 23 countries yielded strong and moderate evidence for lifting, cumulative physical loads, full‐body vibration, and kneeling/squatting/bending as increasing the risks of developing OA in men and women. Strong and moderate evidence existed for no increased risk of OA related to sitting, standing, and walking (hip and knee OA), lifting and carrying (knee OA), climbing ladders (knee OA), driving (knee OA), and highly repetitive tasks (hand OA). Variability in dose‐response data resulted in an inability to synthesize these data. Conclusion: Evidence points to the potential for OA occupational recommendations and practice considerations to be developed for women and men. However, research attention is needed to overcome deficits in the measurement and recall of specific work activities so that recommendations and practice considerations can provide the specificity needed to be adopted in workplaces.